BIM4EarlyLCA: An interactive visualization approach for early design support based on uncertain LCA results using open BIM - Kasimir Forth; Alexander Hollberg; André Borrmann (Developments in the Built Environment, 2023)
To meet the European climate goals in the building sector, a holistic optimization of embodied greenhouse gas (GHG) emissions using the method of life cycle assessments (LCA) are necessary. The early design stages have high impact on the final performance of the buildings and are characterized by high uncertainty due to the lack of information and not yet taken decisions. Furthermore, most current LCA approaches based on Building Information Models (BIM) require high expertise and experience in both BIM and LCA and do not follow an intuitive visualization approach for other stakeholders and non-experts. This paper presents a novel design-decision-making approach for reducing embodied GHG emissions by interactive, model-based visualizations of uncertain LCA results. The proposed workflow is based on open BIM data formats, such as Industry Foundation Classes (IFC) and BIM Collaboration Format (BCF), and is developed for decision support for non-LCA experts in the early design stages. With the help of a user study, the prototypical implementation is tested by 103 participants with different levels of experience in BIM and LCA based on a case study. We evaluate the proposed approach regarding the support of open BIM data formats, different LCA visualization strategies, and the intuitiveness of different approaches to visualizing uncertain LCA results. The user study results show a broad acceptance and need for open BIM data formats and model-based LCA visualization but less for visualizing uncertainties, which needs further research. In conclusion, this interactive, model-based visualization approach using color coding supports non-LCA experts in the design decision-making process in early design stages.